INFLUENCE OF STAFFING LEVELS ON QUALITY OF EDUCATION IN PUBLIC SECONDARY SCHOOLS IN MURANG'A COUNTY, KENYA - Mwaniki, Wilson; Ogola, Martin; Nyerere , Jackline (Journal of Human Resource and Leadership, 2022)
Statement of the Research Problem: Teaching staff is crucial in the provision of quality education in public secondary schools. However, in Murang'a County, many public secondary schools registering a low quality of education. Purpose of the Study: This study aimed at determining the influence of staffing levels on quality of education in public secondary schools in Murang'a County, Kenya. Methodology: The study adopted a correlation research design. This study targeted 292 principals and 3206 teachers totaling 3498 from which a sample of 360 respondents (10.3%) was determined using Yamane's Formula. Using stratified sampling, eight strata considering sub-counties were created. From every sub-county, three principals were selected using purposive sampling. However, from each sub-county, 42 teachers (14 teachers per school) were selected using simple random sampling to avoid bias. Questionnaires were used to gather information from principals and teachers whereas a documentary checklist guide was used by the researcher. Quantitative data were analyzed using descriptive statistics such as frequencies and percentages and inferentially using Pearson's Product Moment Correlation Analysis with the help of Statistical Packages for Social Sciences (SPSS 23) and presented by using tables. Research Findings: The study established that students' academic performance in national examinations (KCSE) is low, students' completion rates with quality grades (C+ and above) are on a decreasing trend and levels and frequency of participation in co-curricular activities are low. From the study findings, the student-teacher ratio in public secondary schools is high owing to the high number of students enrolled courtesy of the Free Day Secondary Education Policy. This implies that, by having an inadequate number of teachers, it is difficult to attend to academic and other delegated duties and thus, not possible to accord students individual attention, which is the essential aspect of quality education. Unique Contribution to Theory, Policy and Practice: The findings of this study lend credence to the premise of the Education Production Function Theory since it revealed that there is a correlation between instruction resources and quality of education. As a practice, secondary schools should engage in alternative income-generating activities to acquire more financial resources to hire more teachers to supplement government's efforts to bridge the gap in the student-teacher ratio. As a policy, the government should ensure adherence to the policy on fair distribution of teachers based on the number of students.